Prevalence of precancerous cervical lesions and associated factors among HIV-positive women in Zewditu Memorial Hospital, Addis Ababa, Ethiopia - Dinberia, Abebech Haile; Ayele, Habtamu Molla; Wodajo, Meaza Zeleke (Frontiers in Oncology, 2025)
BackgroundCervical cancer is one of the major causes of morbidity and mortality among women in low- and middle-income countries. This problem is more severe in developing countries than in developed countries. This study was designed to identify the prevalence and determinants of precancerous cervical lesions among HIV-positive women in the Zewditu Memorial Hospital, Addis Ababa, Ethiopia.ObjectiveThis study aimed to assess the prevalence of precancerous cervical lesions and associated factors among HIV-positive women in Zewditu Memorial Hospital, Addis Ababa, Ethiopia.MethodsAn institution-based, cross-sectional, quantitative study was conducted. The sample size for the study was 361, which was calculated using a single population proportion method, and the final study participants were HIV-positive clients who were eligible for cervical cancer screening and selected using a simple random sampling method. Data were collected from each study participant using an interviewer-administered questionnaire. Data were then entered into Epi Info version 7, cleaned, and analyzed using SPSS version 25. Bivariable and multivariable logistic regression analyses were used to examine the relationship or statistical association between the independent and dependent variables, and odds ratios with 95% confidence intervals were computed.ResultsA total of 361 women who had follow-ups at an antiretroviral therapy clinic were included in the study. The prevalence of precancerous cervical lesions was 16.6%. Having a history of sexually transmitted disease [adjusted odds ratio (AOR) = 4.88, 95% confidence interval (CI): 1.66–14.36, p-value = 0.004], a history of smoking (AOR = 9.35, 95% CI: 3.15–27.75, p-value = 0.000), and abortion (AOR = 3.23, 95% CI: 1.58–6.58, p-value = 0.001) were significantly associated with precancerous cervical lesions.Conclusion and recommendationsThe prevalence of precancerous cervical lesions in this study was high. A history of abortion, smoking, and sexually transmitted infections were strongly associated with precancerous cervical lesions among women with human immunodeficiency virus. Hence, it is important to emphasize the importance of preventing sexually transmitted infections and repeated abortions, as well as discouraging cigarette smoking.